German Heart Surgery Report 2019: The Annual Updated Registry of the German Society for Thoracic and Cardiovascular Surgery - Beckmann, Andreas; Meyer, Renate; Lewandowski, Jana; Markewitz, Andreas; Gummert, Jan (The Thoracic and Cardiovascular Surgeon, 2020)
Based on a longtime voluntary registry, founded by the German Society for Thoracic and Cardiovascular Surgery (GSTCVS) in 1980, well-defined data of all cardiac, thoracic, and vascular surgery procedures performed in 78 German heart surgery departments during the year 2019 are analyzed. For this period, a total of 175,705 procedures were submitted to the registry, 100,446 summarized as heart surgery procedures in a classical sense. The unadjusted in-hospital survival rate for the 34,224 isolated coronary artery bypass grafting procedures (relationship on-/off-pump 3.8:1) was 97.3%. For the 36,650 isolated heart valve procedures (16,625 transcatheter interventions included), it was 96.4%. Concerning short- and long-term circulatory support, a total of 2,716 extracorporeal life support/extracorporeal membrane oxygenation implantations, resp. 953 assist device implantations (L-/ R-/ BVAD, TAH) were registered. In 2019, the number of isolated heart transplantations increased to 333, a rise of 6.7% compared to the previous year. The isolated lung transplantations amounted to 311, a decrease of 8.5%. This annually updated registry of the GSTCVS represents voluntary public reporting by accumulating actual information for nearly all heart surgical procedures in Germany, constitutes advancements in heart medicine, and represents a basis for quality management for all participating institutions. In addition, the registry demonstrates that the provision of cardiac surgery in Germany is up to date, appropriate, and nationwide patient treatment is guaranteed all the time.
Keywords: heart valve surgery; outcomes; congenital heart disease; coronary artery bypass grafting; aortic surgery; heart/lung transplantation